The impact of heavy work investment on the economy and the individual - Simona Roxana Pătărlăgeanu; Carmen Valentina Rădulescu; Mihai Dinu; Marius Constantin (Amfiteatru Economic Journal, 2020)
Heavy work investment represents a research area which has been intensively debated in the specialised literature, especially since 2013. On the one hand, heavy work investment can be made in the means of production, in order to increase work productivity. On the other hand, it is correlated with numerous other factors related to the quality of life and the quality of work conditions, among which: the relationship between work - living standard - personal life; workaholism and technology; the decision to retire and so on. The objectives of this research are to identify the correlations between the quality of life and heavy work investment, as well as to assess the social and economic progress from the view point of the need for heavy work investment. The research methods used in the study were mainly of a quantitative nature: bibliometric and econometric analysis (linear regression with cross-section data). The data used in the econometric models constructed were taken over from two sources: Eurostat and the World Bank. The research findings highlight the fact that in the analysed European states, making work investments by increasing the work volume is not a justified measure, because its effects do not reflect directly on the social and economic progress, quantified as the nominal gross domestic product.
Keywords: C31; J0; I3; 330; heavy work investment; time as a resource; nominal gross domestic product; life expectancy at birth; knowledge society